Variation in the Major Surface Glycoprotein Genes in Pneumocystis jirovecii - Kutty, Geetha (2008)
The genome of Pneumocystis, which causes life-threatening pneumonia in immunosuppressed patients, contains a multi-copy gene family that encodes the major surface glycoprotein (Msg). Pneumocystis can vary the expressed Msg, presumably as a mechanism to avoid host immune responses. Analysis of 24 msg gene sequences obtained from a single human Pneumocystis isolate demonstrated that the sequences segregate into two branches. Based on a number of analyses, recombination among msg genes appears to be an important mechanism for generating msg diversity. Intra-branch recombination occurred more frequently than inter-branch recombination. Restriction fragment length polymorphism analysis demonstrated substantial variation in the repertoire of the msg gene family among isolates of human Pneumocystis, which was not observed in laboratory isolates of rat or mouse Pneumocystis; this may be the result of examining outbred vs. captive populations. Increased diversity in the Msg repertoire, generated in part by recombination, increases the potential for antigenic variation in this abundant surface protein.